A case of completely responding stage D2 prostatic cancer with no evidence of disease 14 years after diagnosis - Tsuzuki, M (Hinyokika kiyo. Acta urologica Japonica, 1994)
A 58-year-old male complaining of pollakisuria, miction pain and back pain visited us Dec. 26, 1979. Rectal examination revealed the prostate enlarged by 5 digital width, stony hard and irregular. Transrectal needle biopsy revealed moderately differentiated adenocarcinoma of the prostate. Bladder neck invasion, pelvic and mediastinal lymph node metastases and multiple bone metastases were found. The case was diagnosed with prostatic adenocarcinoma T3N2M1 (OSS, LYM) stage D2. Three courses of chemotherapy using ifosfamide applied from Feb. 2, 1980 showed no marked effect except for partial pain relief. Hormonal treatment with diethylstilbestrol diphosphate was started from May 28 and arterial infusion chemotherapy using CDDP and 5-FU was performed 2 months later, resulting in size reduction of the prostate and pelvic lymph node metastases and disappearance of mediastinal lymph node metastases. Needle biopsy of the prostate was negative for cancer cells. After 8 months, Tegafur was started, and 12 months later radiotherapy was added to the prostate and pelvic lymph nodes. The abnormal accumulation in bone scan began to decrease after 14 months and achieved complete remission 28 months after the initial therapy. We discontinued the hormonal therapy 31 months later because of his complaint of chest discomfort and palpitation. At the present time, 14 years after the initial therapy, the prostate was 35 x 29 x 19 mm in size on transrectal ultrasonography with undetectable serum PSA level and no tumor cells but only mass fibrosis has been seen by pathological examinations. We considered this patient to be with no evidence of disease